Mitochondrial ROS in Slc4a11 KO Corneal Endothelial Cells Lead to ER Stress - Shyam, Rajalekshmy; Ogando, Diego G.; Bonanno, Joseph A. (Frontiers in Cell and Developmental Biology, 2022)
Recent studies from Slc4a11-/- mice have identified glutamine-induced mitochondrial dysfunction as a significant contributor toward oxidative stress, impaired lysosomal function, aberrant autophagy, and cell death in this Congenital Hereditary Endothelial Dystrophy (CHED) model. Because lysosomes are derived from endoplasmic reticulum (ER) – Golgi, we asked whether ER function is affected by mitochondrial ROS in Slc4a11 KO corneal endothelial cells. In mouse Slc4a11-/- corneal endothelial tissue, we observed the presence of dilated ER and elevated expression of ER stress markers BIP and CHOP. Slc4a11 KO mouse corneal endothelial cells incubated with glutamine showed increased aggresome formation, BIP and GADD, as well as reduced ER Ca2+ release as compared to WT. Induction of mitoROS by ETC inhibition also led to ER stress in WT cells. Treatment with the mitochondrial ROS quencher MitoQ, restored ER Ca2+ release and relieved ER stress markers in Slc4a11 KO cells in vitro. Systemic MitoQ also reduced BIP expression in Slc4a11 KO endothelium. We conclude that mitochondrial ROS can induce ER stress in corneal endothelial cells.